On Topological Descriptors of Certain Metal-Organic Frameworks - Peng Xu; Mehran Azeem; Muhammad Mubashir Izhar; Syed Mazhar Shah; Muhammad Ahsan Binyamin; Adnan Aslam (Journal of Chemistry)
Topological indices are numerical numbers that represent the topology of a molecule and are calculated from the graphical depiction of the molecule. The importance of topological indices is due to their use as descriptors in QSPR/QSAR modeling. QSPRs (quantitative structure-property relationships) and QSARs (quantitative structure-activity relationships) are mathematical correlations between a specified molecular property or biological activity and one or more physicochemical and/or molecular structural properties. In this paper, we give explicit expressions of some degree-based topological indices of two classes of metal-organic frameworks (MOFs), namely, butylated hydroxytoluene- (BHT-) based metal-organic (M=Co, Fe, Mn, Cr) (MBHT) frameworks and M1TPyP−M2 (TPyP = 5,10,15,20-tetrakis(4-pyridyl)porphyrin and M1,M2 = Fe and Co) MOFs.